Time‐Latitude Distribution of Prominences for 10 Solar Cycles: A Study Using Kodaikanal, Meudon, and Kanzelhohe Data. Issue 3 (14th March 2020) - Chatterjee, Subhamoy; Hegde, Manjunath; Banerjee, Dipankar; Ravindra, B.; McIntosh, Scott W.
Abstract: Solar prominences are structures of importance because of their role in polar field reversal. We study the long‐term variation of the time latitude distribution of solar prominences in this article. To accomplish this, we primarily used the digitized disc‐blocked Ca II K spectroheliograms as recorded from Kodaikanal Solar Observatory for the period of 1906–2002. For improving the data statistics we included full disc H α images from Meudon and Kanzelhohe Observatory, which are available after 1980. We developed an automated technique to identify the latitudinal locations of prominences in daily images from all three data sets. Derived time‐latitude distribution clearly depicted poleward migration of prominence structures for 10 cycles (15–24). Unlike previous studies, we separated the rate of poleward migration during onset and near pole, using piece‐wise linear fits. In most cases, we found acceleration in poleward migration with the change occurring near ± 70° latitudes. The derived migration rates for such large number of solar cycles can provide important inputs toward understanding polar field buildup process. Key Points: Calibration of Ca II K disc‐blocked digitized images as recorded in Kodaikanal observatory for the period of 1906–2002 Automated detection of prominences for 10 solar cycles (1906–2018) using images from Kodaikanal, Meudon and Kanzelhohe Observatory Clear identification of nonlinear poleward migration, estimation of migration rates through piecewiselinear fits for 10 solar cycles